Factors Affecting Employees’ Trust in Management - Ghimire, Binod (NCC Journal, 2019)
Employees’ commitment is an important issue in an organization which is the outcome of sense of trust. All relationships and interactions are formed and based in the sense of trust. It is equally important in workplace relationship. Trust tends to have a strong impact on the relationships between hospital managers and nursing employees. It increases commitment level of nurses. This study focuses on three components of trust in management: competency, integrity and benevolence. The aim of this study is to understand factors affecting employees’ trust in the management among nursing employees of hospitals in Nepal. Nurses are the crucial human resources in health care organization and their commitment play vital role for the overall objective of the hospitals. This study is an analytical and descriptive study based on nursing employees. Using multi-stage purposive sampling, four hundred sixty five nurses were chosen as a sample of the study. This research paper advances a theoretical model stating the factors affecting the employees’ trust in management resulted into three variables.